Research and practice on oil displacement law of different well pattern in offshore oilfield. Issue 5 (2nd November 2021) - Wang, Peng; Wang, Shaopeng; Zhang, Hongyou; Sun, Guangyi; Zhai, Shangqi; Chang, Huijiang; Zhang, Chengli
ABSTRACT: BZ oilfield is the first oilfield successfully developed with large-scale horizontal well pattern in Bohai sea. In order to study the well pattern suitable for offshore fluvial sedimentary oilfield, based on the characteristics of offshore oilfield, such as large well spacing, few wells and complex well pattern, the authors designed a set of heterogeneous reservoir models under the guidance of similarity theory. The different well patterns, different displacement rates and different heterogeneity were simulated. The different displacement effects were studied by measuring the electrical characteristics, injection volume, oil production and water production of the model. It is found that the horizontal well pattern is used for low-speed development, the water breakthrough of oil wells is slow in the relatively homogeneous reservoir. In the heterogeneous high permeability reservoir(Jk  = 4), the oilfield adopts low-speed development by using staggered well pattern, the water breakthrough of the oil well is slow, and the EOR is large. In the heterogeneous high permeability reservoir(Jk  = 6), the oilfield adopts the combined well pattern for low-speed development, the EOR is large. This study deepens the understanding of the development law of horizontal well pattern and the distribution law of remaining oil, and provides a basis for oilfield development and adjustment.